Parteneriatul public-privat în România: o oportunitate ratată - Octavian MOLDOVAN (Revista Transilvană de Ştiinţe Administrative, 2017)
Although Romanian public and private (or non-governmental) organizations developed multiple forms of collaboration in the last two decades, none of these joint projects/programs/actions or activities took the form of a legally established public-private partnership (PPP). This policy failure becomes even more problematic considering that the initial legal framework for PPPs was developed and enacted since 2010 (Law no. 178/2010) and both public institutions as well as private or non-governmental organizations often showed openness to such partnerships (at least at a declarative level). Although a new legislation was adopted at the end of 2016 (namely Law no. 233/2016), looking back at the previous legislation can shed some light on this less than successful attempt at reforming and innovating Romanian public administration and the provision of public services. Going beyond a simple review of the theoretical underpinnings of PPPs, this paper analyzes specific administrative developments in Romania as well as the previous legislative approach set to provide legal foundations and backgrounds for public-private partnerships, while also taking into account similar developments at the European level.